Can surgery follow the dictates of the pandemic "keep your distance"? Requirements with COVID-19 for hygiene, resources and the team - Krüger, Colin M.; Kramer, Axel; Türler, Andreas; Riediger, Hartwig (German Medical Science GMS Publishing House, 2020)
Since the beginning of the pandemic, there have been restrictions in the daily care of surgical patients - both elective and emergency. Readying supply capacities and establishing isolation areas and areas for suspected cases in the clinics have led to keeping beds free for treating (suspected) COVID-19 cases. It was therefore necessary to temporarily postpone elective surgery. Now, elective care can be gradually resumed with the second phase of the pandemic in Germany. However, it remains the order of the day to adapt pre-, intra- and post-operative procedures to the new COVID-19 conditions while maintaining specialized hygiene measures. This concerns the correct procedure for the use of personal protective materials as well as process adjustment for parallel treatment of positive and negative patients in the central OR, and handling of aerosols in the operating theater, operating room, and surgical site under consideration of staff and patient protection. Although dealing with surgical smoke in the operating theater has long been criticized, COVID-19 is forcing a renaissance in this area. Finally, the choice of surgical method, whether open surgery or minimally invasive procedures, is critical in determining how many colleagues are exposed to the risk of infection from COVID-19 patients, sometimes for hours. Here, robot-assisted surgery can comply with the pandemic's requirement to "keep your distance" in a unique way, since the surgeon can operate at virtually any distance from the surgical site, at least with regard to aerosol formation and exposure.